2017
DOI: 10.1002/jbm.a.36229
|View full text |Cite
|
Sign up to set email alerts
|

Response of umbilical cord mesenchymal stromal cells to varying titanium topographical signals

Abstract: A wide variety of titanium implant modifications have been developed to improve tissue-or cell-material interactions including bone bonding, implant failure, and contact osteogenesis. Osteogenesis can be stimulated by mechanobiological signals such as topography though translation of in vivo reactions to in vitro bioactivity and stem cell culture data, and vice versa, is challenging. We hypothesized that a systematic in vitro approach comparing clinically wellaccepted implant surface topographical modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…When investigating OPN and OPG expressions of cells cultured on BG and TCPS, interestingly, values were less on all bioglass surfaces compared to TCPS (except OPN for the OIM‐treated samples). This could be caused by a lower cell amount on bioglass samples because of the transfer to new wells on day 1 leaving behind some cells on the well plate bottom similar as observed by others . Thus, less cells expressed less proteins.…”
Section: Discussionmentioning
confidence: 78%
“…When investigating OPN and OPG expressions of cells cultured on BG and TCPS, interestingly, values were less on all bioglass surfaces compared to TCPS (except OPN for the OIM‐treated samples). This could be caused by a lower cell amount on bioglass samples because of the transfer to new wells on day 1 leaving behind some cells on the well plate bottom similar as observed by others . Thus, less cells expressed less proteins.…”
Section: Discussionmentioning
confidence: 78%
“…Based on the average distances between roughness peaks measured for the surfaces in this work (160–193 μm), they are expected to support attachment of osteoblasts and their precursors and finally ingrowth of bone. in vitro studies with mesenchymal stromal cells cultured on comparable TiAl6V4 surfaces (corundum‐blasted and titanium plasma sprayed) showed that the attached cells underwent a change of morphology from 2D to 3D on the microstructures and macrostructures and finally filled the porous surfaces completely (Lauria et al, ). In addition, a beneficial effect of porous titanium plasma sprayed surfaces on the osteogenic differentiation was described (Lauria et al, ; Saldaña, González‐Carrasco, Rodríguez, Munuera, & Vilaboa, ).…”
Section: Discussionmentioning
confidence: 99%
“…in vitro studies with mesenchymal stromal cells cultured on comparable TiAl6V4 surfaces (corundum‐blasted and titanium plasma sprayed) showed that the attached cells underwent a change of morphology from 2D to 3D on the microstructures and macrostructures and finally filled the porous surfaces completely (Lauria et al, ). In addition, a beneficial effect of porous titanium plasma sprayed surfaces on the osteogenic differentiation was described (Lauria et al, ; Saldaña, González‐Carrasco, Rodríguez, Munuera, & Vilaboa, ). Surface treatments aiming at the modification of physical features lead inevitably to the modification of chemical properties, too.…”
Section: Discussionmentioning
confidence: 99%
“…The application of different ions, as another successful method for promoting mesenchymal cell proliferation has been supported by articles of in vitro studies: Yusa et al (2011Yusa et al ( , 2016, Galli et al (2013), Burghardt et al (2015), Lauria et al (2018).…”
Section: Main Textmentioning
confidence: 98%
“…The study is of review type using the keywords: mesenchymal cells implant surface, differentiation, and their combination with the aim of finding logical connections between the activity of mesenchymal cells and possible and different modifications of the implant surface. The search was conducted in several attempts to find articles, (Esfahanian et al 2012) where gradually from 259 articles it was narrowed the list at 73 articles and after the elimination of articles in accordance with the criteria of non-inclusion and during the reading and analysis phase of abstracts, at the end of the electronic search, was a total of 36 articles, available for further and detailed analysis, in accordance with the purpose of the study (Omar et al 2011;Wang et al 2014;Herranz-Diez et al 2016;Chang et al 2016;Hyzy et al 2017;D' Alimonte et al 2017;Guillem-Marti et al 2019;Smaranda Dana Buduru 2019;Bressel et al 2017;Yusa et al 2011Yusa et al , 2016Galli et al 2013;Burghardt et al 2015;Lauria et al 2018;Zhou and Zhao 2016;Yu et al 2017;Manfredi et al 2016;Calzado-Martín et al 2011;Wei et al 2019;Singhatanadgit et al 2019;Kwon and Park 2018;Sagomonyants et al 2011;Maleki-Ghaleh et al 2015;Yang et al 2015;Hao et al 2016;He et al 2016;Zhou et al 2017;Ping et al 2017;Li et al 2017;Zheng et al 2017;Tsuchiya et al 2018;Shao et al 2018;Chen et al 2018;…”
Section: Main Textmentioning
confidence: 99%